Technology in intergenerational exchanges: Young and elderly people work together to improve their Personal Learning Environments - Tur, Gemma (Formazione & insegnamento, 2012)
Technology plays a pivotal role in contemporary society, especially as far as lifelong learning and social inclusion are concerned. Researching how technology is being used by the most elderly learners highlighted the following: lower usage (compared to the youths), the existence of barriers linked to lack of accessibility, together with a positive attitude on behalf of users. Technology is included, as a subject matter, in the courses of the Open University for Seniors, which is affiliated to the Balearic Islands University (Ibiza, Spain). It has, among its grounding themes, people's approach to technology. Adults and children meet to share their experiences concerning ICT and education. Data collected during this case study illustrate how the most mature ICT users deal with technology, as well as their perceptions concerning usage on behalf of the youngest.